2015
DOI: 10.1093/ntr/ntv123
|View full text |Cite
|
Sign up to set email alerts
|

The Cost of Smoking in California

Abstract: Despite extensive efforts at tobacco control in California, healthcare and lost productivity costs attributable to smoking remain high. Compared to costs for 1999, the total cost was 15% greater in 2009. However, after adjusting for inflation, real costs have fallen by 13% over the past decade, indicating that efforts have been successful in reducing the economic burden of smoking in the state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 10 publications
1
28
0
Order By: Relevance
“…Current smoking was reported by 15% of our sample compared to 21% observed by Beesley et al in cervical cancer survivors, 4 and 10% in healthy women participating in the 2009 California Health Interview Survey (CHIS). 38 Approximately 63% of our sample did not meet recommended guidelines for physical activity, similar to the 61%–70% reported in other studies of cancer survivors 4,6 and to the 68% reported for healthy California women in the 2005 CHIS. 39 While alcohol consumption is difficult to compare due to the categorical response, 9% of cervical cancer survivors consumed 4–10 alcoholic drinks per week while 4% reported consuming >10 per week.…”
Section: Discussionsupporting
confidence: 78%
“…Current smoking was reported by 15% of our sample compared to 21% observed by Beesley et al in cervical cancer survivors, 4 and 10% in healthy women participating in the 2009 California Health Interview Survey (CHIS). 38 Approximately 63% of our sample did not meet recommended guidelines for physical activity, similar to the 61%–70% reported in other studies of cancer survivors 4,6 and to the 68% reported for healthy California women in the 2005 CHIS. 39 While alcohol consumption is difficult to compare due to the categorical response, 9% of cervical cancer survivors consumed 4–10 alcoholic drinks per week while 4% reported consuming >10 per week.…”
Section: Discussionsupporting
confidence: 78%
“…The California Tobacco Control Program (CTCP) has demonstrated significant reductions in overall smoking initiation (Messer et al, 2007; Pierce, Messer, White, Cowling, & Thomas, 2011; Pierce, White, & Gilpin, 2005), cigarette consumption (Al-Delaimy, White, Gilmer, Zhu, & Pierce, 2008; Gilpin, Messer, White, & Pierce, 2006; Pierce, White, & Messer, 2009), and associated reductions in cardiovascular and cancer morbidity and mortality rates (Lightwood & Glantz, 2013; Max, Sung, Shi, & Stark, 2015). As a result, California reaped an overall savings of $134 billion in healthcare expenditures for the state (Lightwood & Glantz, 2013; Max et al, 2015). As a whole, the US has also seen declines in tobacco use and savings due to reductions in health care expenditures and increases in quality of life measures (US Department of Health and Human Services, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The clinic-based controls included a smaller proportion of former smokers and more never smokers in comparison to our earlier population-based controls. Successful policy initiatives to reduce smoking in California may be reflected in the declining association between cigarette smoking and PC in the SFBA between our Panc1 and our Panc2 studies[38][39][40].…”
mentioning
confidence: 99%